2017
DOI: 10.21873/anticanres.11818
|View full text |Cite
|
Sign up to set email alerts
|

Potential Implication of Paxillin in Cancer Establishment Within the Bone Environment

Abstract: These data suggest that paxillin appears to influence major cell functions in a diverse range of prostate and breast cancer models. The responsiveness of cells to environmental factors such as HGF or BME may be influenced by paxillin status, although this seems to be dependent on cell type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Overexpression of Paxillin has been reported in a number of different human cancer types ( Sobkowicz et al, 2017 ; Deakin et al, 2012 ; Yang et al, 2010 ; Salgia et al, 1999 ; Mackinnon et al, 2011 ). However, there are far fewer studies investigating Paxillin phosphorylation in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Paxillin has been reported in a number of different human cancer types ( Sobkowicz et al, 2017 ; Deakin et al, 2012 ; Yang et al, 2010 ; Salgia et al, 1999 ; Mackinnon et al, 2011 ). However, there are far fewer studies investigating Paxillin phosphorylation in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Paxillin has been reported in a number of different human cancer types (Deakin et al, 2012; Mackinnon et al, 2011; Salgia et al, 1999; Sobkowicz et al, 2017; Yang et al, 2010). However, there are far fewer studies investigating Paxillin phosphorylation in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…The cyclic regulation of FA is a key step in the control of cell adhesion and motility. Paxillin and FAK are key components of focal adhesions and changes in their expression or localization and their phosphorylation status are often associated with cancer cell metastasis [51]. Studies have shown that pS178-paxillin can promote the reorganization of FA to promote the migration of pancreatic tumor cells [52].…”
Section: Paxillin Regulates Tumor Cell Migrationmentioning
confidence: 99%
“…In the prostate cancer cell line PC-3 osteolytic model and the mixed osteolytic/osteogenic LNCaP model, paxillin knockdown resulted in reduced matrix adhesion and a general increase in cell invasion, but the opposite occurred in the MDA-MB-231 breast cancer model. Therefore, paxillin is considered to have potential specific effects in different cell lines or cancer types [51].…”
Section: Paxillin Regulates Tumor Cell Invasive Metastasismentioning
confidence: 99%